2019
DOI: 10.1159/000496480
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fluorescent Clinical Method to Rapidly Quantify Plasma Volume

Abstract: Objectives: To determine the performance of a rapid fluorescent indicator technique for measuring plasma volume (PV). Methods: This was an open-label, observational evaluation of a two-component intravenous visible fluorescent dye technique to rapidly measure PV in 16 healthy subjects and 16 subjects with chronic kidney disease (8 stage 3 and 8 stage 4 CKD), at 2 clinical research sites. The method consisted of a single intravenous injection of 12 mg of a large 150-kDa carboxy-methyl dextran conjugated to a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Though no severe adverse events were considered related to the VFI compound, a subset of patients exhibited mild or moderate events suggestive of allergic reactions, including two cases of transient pruritus and urticaria, which resolved within 30–60 min after antihistamine treatment. A previously published study using VFI reported no serious adverse events 24,31 . Placebo‐controlled data on the VFI compound are currently limited to one small Phase 1 study, in which VFI or placebo was administered in 32 healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Though no severe adverse events were considered related to the VFI compound, a subset of patients exhibited mild or moderate events suggestive of allergic reactions, including two cases of transient pruritus and urticaria, which resolved within 30–60 min after antihistamine treatment. A previously published study using VFI reported no serious adverse events 24,31 . Placebo‐controlled data on the VFI compound are currently limited to one small Phase 1 study, in which VFI or placebo was administered in 32 healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…PV is calculated from the measured blood volume, venous hematocrit, corrected for the trapped plasma and mean body hematocrit. 29 Recently, a non-isotopic (fluorescent) method to rapidly quantify PV and renal function was developed. The method consists of 12mg of a 150-kDa carboxy-methylated dextran, conjugated to a rhodamine dye (plasma volume marker), and 35mg of a 5-kDa carboxy-methylated dextran, conjugated to fluorescein (renal clearance marker), in a total volume of 3.0 ml.…”
Section: I-hsa Methods 28mentioning
confidence: 99%
“…The injectate is infused intravenously over 30s. Dye concentrations are quantified at only 1-time point, 15 min after the injections for initial PV measurements using the indicator-dilution principle, and this timing may have less influence on the value of PV 29 . Blood volumes are calculated based on PV and the subject's hematocrit.…”
Section: I-hsa Methods 28mentioning
confidence: 99%
See 2 more Smart Citations